Monitoring of Serum Levels of Angiogenin, ENA-78 and GRO Chemokines in Patients with Renal Cell Carcinoma (RCC) in the Course of the Treatment - Dagmar Hlávková (Acta Medica, 2008)
Tumour progression requires the presence of a rich vascular supply. A number of cytokines, chemokines and proteases participate in the process of tumour angiogenesis. We evaluated serum levels of angiogenin, panGRO (Growth Related Oncogene) (CXCL 1,2,3) and ENA-78 (Epithelial Neutrophil Activating) (CXCL5) in the serum of 32 patients with RCC (renal cell carcinoma) and 14 healthy blood donors by means of a protein array analysis. The patients were divided into three groups according to their disease stages (I+II, III, IV). We discovered significant differences between the blood donors and patients with RCC both in pre-operative and post-operative angiogenin, panGRO and ENA-78 levels. The increase in angiogenic factors lasted in patients even without metastases 2 months after surgery. We found no correlation between the levels of angiogenin and stages I+II, III and IV RCC. Patients with advanced carcinoma (stage III) had pre-operatively higher serum levels of ENA-78 than patients with stages I+II (p = 0,009) and IV (p< 0.001). Eight weeks after surgery the patients with stages I+II had significantly higher levels of panGRO than patients with stage IV.